1999
DOI: 10.1111/j.1748-0361.1999.tb00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer and Provider Evaluation of Rural Pharmacy Services

Abstract: This paper compares consumer and provider perceptions regarding access to pharmacy services in rural Illinois, given a decrease in the number of pharmacies. Consumer data are from the Illinois Rural Life Panel in which more than 1,800 respondents answered questions about availability and use of pharmacy services and about insurance coverage and cost. A survey of all licensed retail pharmacies in 74 rural Illinois counties and in seven non-rural counties provided pharmacy background information and was the sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…not report on the availability of a pharmacy in the same town or the distances traveled to obtain pharmacy services. Straub and Straub (1999) reported that 77% of rural Illinois residents surveyed had a pharmacy in their community; less than 2% of these residents were more than 11 miles away from their local pharmacy.…”
mentioning
confidence: 99%
“…not report on the availability of a pharmacy in the same town or the distances traveled to obtain pharmacy services. Straub and Straub (1999) reported that 77% of rural Illinois residents surveyed had a pharmacy in their community; less than 2% of these residents were more than 11 miles away from their local pharmacy.…”
mentioning
confidence: 99%
“…Offer written information to all consumers with regular medicine(s) Assess each consumer individually to determine if they need written information, and then give it out to the consumer Assess each consumer individually to determine if they need written information, and then offer it to the consumer Give out written information only if requested by the consumer Other, please specify ……………………………………………………………………………………………….. 13. Please indicate which of the following best describes how you give out CMI leaflets to your consumers with their prescription medicine(s) while providing verbal information?…”
Section: Resultsmentioning
confidence: 99%
“…There is strong evidence that rural residents have high expectations of pharmacy services [11][12][13][14]. The opportunity to communicate with the pharmacist has been reported to be highly valued by rural residents, compared to their urban counterparts [11].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Community pharmacists generally are not categorized as primary care providers, but their accessibility and familiarity with their patients may make them the first health care professional sought when a problem arises. The pharmacist can provide a triage function.…”
Section: Primary Carementioning
confidence: 99%
“…Curative therapy for TB Treatment for high-risk persons with latent TB infection Timely laboratory confirmation of TB cases [14][15] Prevention services for international travelers [14][15][16] Invasive early-onset group B streptococcal disease [14][15][16][17] Peptic ulcer hospitalizations [14][15][16][17][18] Antibiotics prescribed for ear infections [14][15][16][17][18][19] Antibiotics prescribed for common cold [14][15][16][17][18][19][20] Hospital-acquired infections [14][15][16][17][18][19][20][21] Antimicrobial use in intensive care units Vaccination coverage for children in day care, kindergarten, and first grade [14][15][16][17][18][19][20][21][22][23][24] Fully immunized young children and adolescents …”
Section: Documented Impactmentioning
confidence: 99%